Fashion Industry: Analysis of Strategies and Roles of Stakeholders To Realize Indonesia As The Center of Global Halal Fashion - Mawaddatunnisa, Hanna Abimafy; Fatwa, Nur; Nurwahidin, Nurwahidin (Journal Of Middle East and Islamic Studies, 2026)
Indonesia, through the Halal Product Assurance Agency (BPJPH), has launched the Indonesia Global Halal Fashion (IGHF) initiative in collaboration with the textile industry and fashion designers during Indonesia Fashion Week 2024. This initiative aims to position Indonesia as a global hub for halal fashion—distinct from general Muslim fashion by incorporating halal principles throughout the entire production chain. Despite its vast potential, the development of halal fashion in Indonesia still faces challenges, particularly in capturing consumer preferences and defining comprehensive regulatory standards. This study adopts a qualitative approach, integrating SWOT analysis, STP (Segmentation, Targeting, Positioning), and the Quadruple Helix framework to formulate strategic recommendations. The findings highlight Indonesia’s strong potential to lead the global halal fashion market, supported by natural resources, skilled human capital, and collaboration among key stakeholders: government, academia, industry players, and society. The proposed framework serves as a strategic foundation for enhancing marketing effectiveness and advancing policy development in a sustainable and inclusive manner.